Value in assessing new vaccines (Italian Journal of Public Health, 2009)
Vaccination strategies are recognised as one of the most powerful interventions in the field of Public healthworldwide, capable of reducing both morbidity and mortality. There is wide availability of new vaccines, atleast in Developed Countries, that have the potential to control infectious diseases, while on the other handthere are new vaccines that will become available in the next few years. This paper aims to describe thedifferent perspectives one could take into account in valuing particularly new vaccines.The epidemiological approach has been one of underlying principles in setting priorities for immunizationprograms. The introduction in the health market of a new vaccine is based on the assessment of the relatedburden of infection/disease and the consequent impact on population health.In the economic evaluation approach several types of analysis are available. The budget impact analysis isconcerned more with the immediate impact; in this sense cost is considered instead of value as well as givinghigher consideration to short-term effects, while cost-effectiveness or cost-utility analysis can be utilised toexamine effects in the long term.In the field of vaccinations a public approach through the use of media campaigns or non-profit organisations,might or might not push politicians and physicians to take action to address a perceived health problem viaa vaccine.A Health Technology Assessment approach has been developed in some European countries to examine, in amultidisciplinary way, the clinical, economic, organizational, ethical, juridical, social and cultural implicationsof the introduction or the implementation of a specific technology. The HTA approach in Italy wasdemonstrated to be a comprehensive tool in assessing the introduction of a new vaccine, giving insight to theissue to several stakeholders, i.e. decision makers, researchers, and patients.